User Experience Evaluation of the FASANDI UNPAB Website Using the Cognitive Walkthrough Method and Usability Principles - Sri Wahyuni; Virdyra Tasril (Journal of Information Technology, computer science and Electrical Engineering, 2025)
The website of the Faculty of Computational Science and Digital Intelligence (FASANDI) at University of Pembangunan Panca Budi serves as a medium of information about the faculty profile, academics, tuition fees, facilities, and registration procedures. In order for this information to be easily accessible and understandable to users, a user experience (UX) evaluation needs to be conducted. The objective is to analyze the UX on the FASANDI UNPAB website using the Cognitive Walkthrough method with reference to usability principles. This method is used to assess how users, especially new users such as prospective students, complete key tasks on the website without external assistance. The evaluation was carried out by compiling task scenarios such as searching for study program information, viewing faculty profiles, and understanding the registration procedures linked to external portals. The analysis results show that the website has a fairly complete information structure, but several obstacles were found, such as suboptimal navigation consistency, poorly organized menu placement, and a lack of contextual clues to help users understand the flow of information access. In addition, several pages require visual rearrangement so that important elements are more easily visible.